Providing tokens as incentives promotes positive behaviors related to oral hygiene and self-care in individuals with mental illness - Zaenab; Muslih, Muhammad (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Mental disorders, particularly schizophrenia, cause a decline in mental function, impacting individuals' inability to perform self-care activities independently, including dental and oral hygiene. This self-care deficit is caused by cognitive impairment, lack of motivation, and the inability to organize and carry out daily activities. Appropriate interventions are essential to support the restoration of independence and improve patients' quality of life. Purpose: To determine the effectiveness of implementing the token economy method in improving oral hygiene in patients with self-care deficits due to mental disorders. Method: An in-depth case study was conducted on one patient diagnosed with self-care deficit using the token economy method as an intervention. Data were collected through observations, a token economy checklist, and self-care (oral hygiene) activity observation sheets for two weeks, from October 20 to November 1, 2025. Analysis focused on improving the patient's oral hygiene score. Results: After two weeks of the token economy intervention, there was a significant improvement in patients' toothbrushing activity, as measured by token scores. Oral hygiene scores improved from poor (10) to fair (30), with patients showing consistent progress in performing self-care independently. Conclusion: This intervention successfully motivated patients to maintain regular and independent oral hygiene. Keywords: Oral Hygiene; Schizophrenia; Self-Care Deficit.